2003
DOI: 10.32725/jab.2003.032
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of non invasive laser on the process of healing of an extraction wound by infrared thermography: preliminary study

Abstract: The purpose of this preliminary, double-blind, placebo-control study was to evaluate the effect of GaAlAs diode laser on wound healing and pain reduction in patients after extraction of impacted lower third molars by infrared thermography. Material and methods: The study population of two patients was divided into group A treated by GaAlAs diode laser with a wavelength 830 nm and maximal output power of 100 mW and group B treated by placebo laser. Therapeutic Schedule: The energy density per point was 12 J, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Regarding the protocol's timing and the number of sessions, immediate postoperative single-session PBM was the most tested protocol. In a systematic review, it was found that only 1 study out of 17 included studies using both preoperative and postoperative PBM protocols [19,22], and only 2 studies used repeated sessions [38,39]. In a recent randomized clinical trial, the single-session and repeated-session protocols were compared.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the protocol's timing and the number of sessions, immediate postoperative single-session PBM was the most tested protocol. In a systematic review, it was found that only 1 study out of 17 included studies using both preoperative and postoperative PBM protocols [19,22], and only 2 studies used repeated sessions [38,39]. In a recent randomized clinical trial, the single-session and repeated-session protocols were compared.…”
Section: Discussionmentioning
confidence: 99%
“…Absolute contraindications are a danger to eye and thyroid gland irradiation; patients with a malignant ijlpr2022;doi 10.22376/ijpbs/lpr.2022.12.6.SP25.L100-108 L-107 neoplasm, cardiac pacemaker, or epilepsy; and pregnancy. Relative contraindications are local infection, blood disease, photosensitive skin, or use of drugs that cause photosensitivity, and the chance of irradiating the gonads 22,23 .…”
Section: L-106mentioning
confidence: 99%